Colloidal and Dissolved Organic Matter Excreted by a Mixotrophic Flagellate during Bacterivory and Autotrophy - Tranvik, Lars (1994)
Excretion of dissolved and colloidal organic carbon by a mixotrophic flagellate, the chrysophyte Poterioochromonas malhamensis, was studied. Flagellates were incubated either with (14)C-labeled bacteria or with inorganic (14)C, in order to compare organic exudates originating from primary production with exudates originating from ingested bacteria. Colloids of >0.02 μm constituted a larger fraction of the exudates originating from ingested bacteria, compared with exudates derived from primary production. Flagellate feeding on bacteria specifically labeled in different cell components was compared. Cell wall components gave rise to less colloidal organic carbon than did other cell constituents. To investigate the degradability of flagellate (14)C-exudates, they were added to lake water and mineralization to (14)CO(2) was monitored. Bacterially derived exudates were more recalcitrant than exudates originating from photosynthesis. The results support the hypothesis that bacterial utilization of labile organic compounds, followed by flagellate bacterivory and exudation, results in a transformation of labile organic matter into more recalcitrant forms.